Academy of Management Book Awards (Academy of Management Journal, 1966)
This article presents a list of books honored by the Academy of Management as the Best Books in Management for 1962-1965, including “The Management Profession,” by Louis Allen, “Management Rights and Union Interests,” by Margaret Chandler and “Management: Theory and Practice,” by Ernest Dale.